Education, outreach and communication during the International Polar Year 2007-2008: stimulating a global polar community - Salmon, RA; Carlson, DJ; Zicus, Z; Pauls, M; Baeseman, J; Sparrow, EB; Edwards, K; Almeida, MH; Huffman, LT; Kolset, T; Malherbe, RJH; McCaffrey, MS; et al. (The Polar Journal, 2011)
The International Polar Year 20072008 (IPY) represented one of the largest international scientific research efforts ever undertaken. In addition to its goals of making major advances in polar knowledge, stimulating new and enhanced observational systems and infrastructure, and inspiring a new generation of polar scientists and engineers, it also stimulated the active engagement of thousands of teachers, students and citizens around the world through careful cultivation of enthusiastic scientists, educators and communicators and through creative use of free technologies. The establishment of this new global polar community resulted from a deliberate effort to stimulate a sense of polar affinity that extended beyond the relatively select group of people who live, work or visit these regions. This paper describes and assesses those community-building efforts, including international coordination of events, activities and materials, science and education partnerships, and professional recognition for outreach activities.